Literasi Keuangan, Penggunaan E-Money, Kontrol Diri, dan Gaya Hidup Terhadap Perilaku Konsumtif Belanja Online - Yusuf Aulia Rakhman; Tri Kartika Pertiwi (IPM2KPE, 2023)
The purpose of this study was to examine the relationship between financial literacy, use of electronic money, self-control, and lifestyle factors in Generation Z internet shoppers in Surabaya. This research method is quantitative. The sample used in this study consisted of 109 respondents. Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) approach is the analytical method used. The results of the study show, a) the financial literacy variable on consumptive behavior has a path coefficients value of -0.261 and a P value of 0.015 <0.05; b) the electronic money variable on consumptive behavior has a path coefficient value of 0.301 and a P value of 0.019 <0.05; c) the self-control variable on consumptive behavior has a path coefficients value of -0.162 and a P value of 0.033 <0.05; d) the lifestyle variable on consumptive behavior has a path coefficients value of 0.251 and a P value of 0.012 <0.05. In conclusion, although the use of electronic money has a substantial beneficial impact on consumer behavior when shopping online, financial literacy has a large negative impact. Moreover, lifestyle has a strong beneficial impact on consumption when purchasing online while self-control has a large negative impact. Keywords: Electronic Money, Lifestyle, Self Control, Financial Literacy, Consumptive Behavior